ÍNDICE RELATIVO DE CLOROFILA PARA O DIAGNÓSTICO DO ESTADO DE NITROGÊNIO EM HÍBRIDOS DE MILHO - Gruzska, Maurício (2012)
Nitrogen (N) is the nutrient that contributes the most to increase productivity of corn hybrids. For this reason, the main objective of this study is to determine the relative chlorophyll index (RCI), in different leaves and phenological stages, aiming diagnosing N state in corn hybrids according to the N doses applied in coverage, correlating them with the foliar N content and productivity. In addition, we had as objective to study the effect of N doses applied in coverage on corn hybrids concerning growth and corn plant development variables in Guarapuava city - Paraná. To fulfill this objective an open field experiment with no-tillage system was carried out on Jordãozinho Farm, in Entre Rios region, Guarapuava – Paraná – Brazil, from October 1st 2009 to March 20th 2010. The treatments resulted from the combination of two simple corn hybrids (P30R50 and AG8025) and six N doses applied in coverage (0; 75; 150; 225; 300 and 375 kg of N ha-1 in the form of urea), comprising 2x6 factorial arrangement, making up 12 treatments, arranged in randomized block design with 4 repetitions, totaling 48 experimental units. The N state was monitored using chlorophyll meter, clorofiLOG brand, assessing RCI at least twice in each selected leaf. Hybrid corn AG8025 presented fewer leaves, lower RCI in leaf 3 in V4 (RCIL03V4), RCIL05V9, fewer numbers of grain rows per ear and less insertion height of the primary ear than hybrid P30R50, however a higher plant, more total dry phytomass, higher RCI in leaf 13 in R3 and productivity, indicating genetic variability. The N doses influenced variables such as height of plants in V9 and R1, height of the primary ear insertion, thatched diameter, number of photosynthetically active leaves in R1, ear diameter, foliar N content, 1,000 mass grains and productivity. The dose of 295 kg N ha-1 enabled to estimate productivity in 13,032.93 kg ha-1. The hybrid and N dose factors have not influenced the harvest rate, whose average value was 0.52. The hybrids and the N doses concomitantly influenced variables such as number of photosynthetically active leaves in V9, number of grains per row, ear length, dry phytomass of grains per ear and the total of aerial part per plant, RCIL05V7, RCIL07V7, RCIL07V9,RCIL09V9, RCIL11VT, RCIL11R1, RCIL13R2, RCIL15R2, RCIL15R3. The results indicate that the portable chlorophyll meter is sensitive when indicating the nutritional state of corn hybrids as an outcome of N doses applied in coverage in the first stages of development, enabling its usage for precocious nutritional diagnosis, as well as, in the final evaluation of growth and reproductive phases, as an indication of effective nitrogen fertilization. The RCIs showed positive correlation with foliar N content and productivity, except the RCIs in L03V4, L05V5 and L09V9. The correlation coefficients between RCIs and foliar N content, as well as with productivity, increased with the leaf age.